The welfare gains of age related optimal income taxation - Spencer Bastani; Sören Blomquist; Luca Micheletto (Center for Economic Studies and ifo Institute (CESifo), 2010)
Using a calibrated overlapping generations model we quantify the welfare gains of an age dependent income tax. Agents face uncertainty regarding future abilities and can by saving transfer consumption across periods. The welfare gain of switching from an age-independent to an age-dependent nonlinear tax amounts in our benchmark model to around three percent of GDP. The gains are particularly high when there are restrictions on debt policy. The gains of using a nonlinear- as opposed to a linear tax are even larger. Surprisingly, it is of secondary importance to optimally choose the tax on interest income.
Keywords: H21; H23; H24; 330; labor income taxation; capital income taxation; age-dependent taxes; OLG model; Optimale Besteuerung; Einkommensteuer; Altersgruppe; Overlapping Generations; Wohlfahrtseffekt; Theorie